Regulation of IL-1 Receptor Antagonist by TSH in Fibrocytes and Orbital Fibroblasts - Li, Bin (Endocrine Society, 2014)
CONTEXT: The IL-1 family plays important roles in normal physiology and mediates inflammation. The actions of IL-1 are modulated by multiple IL-1 receptor antagonists (IL-1RA), including intracellular and secreted forms. IL-1 has been implicated in autoimmunity, such as that occurring in Graves' disease (GD) and its inflammatory orbital manifestation, thyroid-associated ophthalmopathy (TAO). We have previously reported that CD34(+) fibrocytes, monocyte-lineage bone marrow-derived cells, express functional TSH receptor, the central antigen in GD. When activated by TSH, they produce IL-6, IL-8, and TNF-α. Moreover, they infiltrate the orbit in TAO in which they transition into CD34(+) fibroblasts and comprise a population of orbital fibroblasts (OFs). Little is known currently about any relationship between TSH, TSH receptor, and the IL-1 pathway. OBJECTIVE: The objective of the study was to determine whether TSH regulates IL-1RA in fibrocytes and OFs. DESIGN/SETTING/PARTICIPANTS: Fibrocytes and OFs were collected and analyzed from healthy individuals and those with GD in an academic clinical practice. MAIN OUTCOME MEASURES: Real-time PCR, Western blot analysis, reporter gene assays, and cell transfections were performed. RESULTS: TSH induces the expression of IL-1RA in fibrocytes and GD-OFs. The patterns of induction diverge quantitatively and qualitatively in the two cell types. This results from relatively small effects on gene transcription-related events but a greater influence on secreted IL-1RA and intracellular IL-1RA mRNA stabilities. These actions of TSH are dependent on the intermediate induction of IL-1α and IL-1β. CONCLUSIONS: Our findings for the first time directly link activities of the TSH and IL-1 pathways. Furthermore, they identify novel molecular interactions that could be targeted as therapy for TAO.